Effect of Combination Drill Training on Pointing and Shooting Performance of Petanque Athletes in Kendal Regency: One Group Pretest-Posttest Study - Dewi, Nadia Cinthya; Haryono, Sri; Pratama, Rivan Saghita (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2026)
This Combination drill training has been increasingly utilized to enhance technical performance in precision-based sports; however, empirical evidence regarding its effectiveness in simultaneously improving pointing and shooting skills in petanque remains limited. These two techniques are fundamental indicators of performance, yet they are often trained separately, potentially leading to imbalanced skill development. Therefore, an integrated training approach is needed to optimize both skills concurrently. This study examined the effect of combination drill training on pointing and shooting performance in petanque athletes. A quantitative approach with a one-group pretest–posttest experimental design was employed. The participants consisted of 10 adolescent athletes aged 12–14 years who met the inclusion criteria. The intervention was conducted over 4 weeks, with 3 sessions per week, for a total of 12 training sessions. Each session used a structured combination drill model that integrated pointing and shooting within a single training sequence. Data were analyzed using descriptive statistics and paired-samples t-tests. The results indicated significant improvements in both pointing and shooting performance following the intervention (p < 0.05). The results showed that pointing performance improved from 12.6 ± 3.6 to 20.1 ± 6.7, while shooting performance increased from 7.5 ± 6.5 to 16.9 ± 7.5. Statistical analysis indicated that both improvements were significant (p < 0.05). These findings indicate that combination drill training provides a meaningful improvement in technical performance within a relatively short training duration. In conclusion, combination drill training can be considered an effective approach for simultaneously improving pointing and shooting performance in petanque athletes. Nevertheless, the findings should be interpreted with caution due to the limited sample size and the absence of a control group. Future research is recommended to employ more robust experimental designs to strengthen the generalizability of the results.